Diagnostic imaging in the pregnant bitch: risks, advantages, and disadvantages - Schrank, Magdalena; Pereira, Maria; Mollo, Antonio (Frontiers in Veterinary Science, 2025)
Diagnostic imaging techniques are routinely used in bitches during pregnancy. Ultrasound examination (UE) and radiographic imaging (RI) are the two most frequently employed exams, for pregnancy diagnosis, assessment of fetal vitality and parturition date prediction, and for determination of litter size, respectively. In human medicine, the effects of radiation exposure resulting from diagnostic imaging, as well as radiation thresholds above which the risk of permanent damage to the offspring is significant, are well documented. Although no such information is available in veterinary medicine, breeders are increasingly skeptical about the use of X-rays in bitches in late-stage pregnancy, both because of the potential harm caused by the stress of the exam and because of the direct effects of radiation on the dam and fetuses. Stress is known to exert an effect in the reproductive processes in many species with one of the greatest stressors being the separation of the bitch from the pups for transport to the veterinary clinic during or right after parturition. This review also demonstrates that the harm resulting from radiation exposure from a radiographic study in a bitch during late-stage pregnancy and for its fetuses, who have already completed organogenesis, is poorly researched. While breeders’ hesitations may be perceived as unfounded by the veterinarians, it is crucial that they are taken into consideration and that clear communication between the breeder and veterinarian is established. Owners should be informed of the lack of studies on the subject in the domestic dog but also presented the available information for other species including the human.